Contemplating the future of "development communication" in South Africa today - Simon Burton (Communicare)
This arlicle offers some reffections on the state of development communication in South Africa, and suggests that closer attention needs to paid to the theoretical underpinnings of communication for development' practices, the emerging institutional contexts and the capacity building that is required in a rapid change situation. It suggests that academics and practitioners need to find a middle way through the 'anything goes' and 'developmentalism' poles of the debate about how best to use communication for development. particularly in the light of the new Government Communications and Information Service and the Poverly and Inequality Report.